The Mediating Role of Financial Performance on the Relationship between Capital Structure and ESG performance of Ghanaian Non-Financial Firms - Philipina Ampomah; Denny Andriana; Nugraha Nugraha; Maya Sari; Francis Kortey Mac-Moqu (Universitas Bangka Belitung, 2026)
This study empirically analyzes the mediating effect of financial performance on the relationship between capital structure and the ESG performance of listed non-financial firms in Ghana. Using panel data from 16 firms enlisted on the Ghana Stock Exchange from 2015 to 2024, the study adopts the random-effects model. The results show that (1) both debt and equity capital have a negative influence on ESG performance, corroborating the agency theory; (2) debt capital does not significantly influence financial performance, but equity capital positively influences financial performance, violating the Modigliani and Miller theory; and (3) financial performance has a positive influence on ESG performance, corroborating the resource-based view theory. Further analysis regarding the mediating effect shows that financial performance partially mediates the relationship between capital structure and ESG performance. The study emphasizes the need for managers to be cautious when choosing the optimal capital structure, bearing in mind that improved financial performance is one of the ways their capital structure decisions can enhance ESG performance. The novelty of this study lies in the development and validation of a mediation model of capital structure, financial performance, and ESG performance in a sub-Saharan African context, enhancing our understanding of corporate finance in underdeveloped capital markets.